2012
DOI: 10.1186/1472-6882-12-113
|View full text |Cite
|
Sign up to set email alerts
|

Brahmarasayana protects against Ethyl methanesulfonate or Methyl methanesulfonate induced chromosomal aberrations in mouse bone marrow cells

Abstract: BackgroundAyurveda, the traditional Indian system of medicine has given great emphasis to the promotion of health. Rasayana is one of the eight branches of Ayurveda which refers to rejuvenant therapy. It has been reported that rasayanas have immuno-modulatory, antioxidant and antitumor functions, however, the genotoxic potential and modulation of DNA repair of many rasayanas have not been evaluated.MethodsThe present study assessed the role of Brahmarasayana (BR) on Ethyl methanesulfonate (EMS)-and Methyl meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…However, with EMS at 72 h RT and MMS at 48 and 72 h in both diabetic and non diabetic mice with different doses, the activity of catalase did not exhibit significant changes, thus, it can be opined that the changes in the activity of catalase were not dose dependent. Working in non diabetic mice Guruprasad et al [44] have demonstrated an increase in catalase activity with EMS and decreased activity with MMS treatment which is on par with our studies in non diabetic mice. Salmon et al [45] and Friedberg et al [46] have showed that MMS cannot produce ROS directly, but induced the DNA damage causing an increase in intracellular ROS level in yeast cells.…”
Section: Discussionsupporting
confidence: 86%
“…However, with EMS at 72 h RT and MMS at 48 and 72 h in both diabetic and non diabetic mice with different doses, the activity of catalase did not exhibit significant changes, thus, it can be opined that the changes in the activity of catalase were not dose dependent. Working in non diabetic mice Guruprasad et al [44] have demonstrated an increase in catalase activity with EMS and decreased activity with MMS treatment which is on par with our studies in non diabetic mice. Salmon et al [45] and Friedberg et al [46] have showed that MMS cannot produce ROS directly, but induced the DNA damage causing an increase in intracellular ROS level in yeast cells.…”
Section: Discussionsupporting
confidence: 86%
“…In general, the toxic mechanism of action involves the direct alkylation by type 2 nucleophilic substitution of guanine and adenine, which results in their ability to induce single and double strand breaks, as well as to generate reactive oxygen species [33]. As a whole, the data suggest that the protective effect of the prickly pear juice red-purple variety is associated with the presence of phytochemicals of their own chemical composition, and although our data do not confirm it completely, we think that the anticlastogenic ability is probably attributed to a synergistic antioxidant mechanism between betalains and flavonoids as they are the main components.…”
Section: Discussionmentioning
confidence: 99%
“…EMS was often used as a positive control in genotoxic test, both in in vitro and in vivo test system. The types of chromosomal aberrations induced by EMS as a positive control were reported to be chromosome break, chromatid break (14). According to our knowledge, this is the fi rst study that addresses the antigenotoxic effects of 4-MEI in bone marrow cells of Swiss Albino Mice.…”
Section: Discussionmentioning
confidence: 99%
“…Ethyl methanesulfonate (EMS) well-known mutagenic and clastogenic agents in in vivo test system were used as a genotoxic agent (14). Sub-lethal high doses of EMS (240 mg/kg b.w) was employed (12 or 24 hours before sacrifi ced of the animals), as earlier established by Riaz and Vasudev (15).…”
Section: Ems Administrationmentioning
confidence: 99%